A Comparative Study between the Role of Religious Orientations and Personality Dimensions in the Prediction of coping Strategies in Mothers of Children with and Without Intellectual Disability - Mahmoud Khabaz; Yaser Rezapour-Mirsaleh; Kianoush A'bdi; Mohammad Hadi Safi (University of Social Welfare and Rehabilitation Sciences, 2011)
Objectives: The purpose of present study was to investigate and compare religious orientation and personality dimensions in the prediction of coping strategies in mothers of children with and without intellectual disability (ID). Materials and Methods: In this descriptive study, a total of 124 mothers of children with ID and 124 mothers of children without ID from 5th and 6th regions of Tehran city were selected through a cluster sampling method. Outcome measures were included Islamic Religious Scale, five factors personality questionnaire and coping strategies questionnaire. Data were analyzed using correlation and regression analysis. Results: Between groups analysis demonstrated that religious beliefs particularly religious pretentiousness had an important role in the prediction of problem-focused coping in mothers of children with ID compared with mothers of children without ID. Among personality dimensions, neuroticism dimension had a significant role in the prediction of emotion-focused coping in mothers of children with ID (P=0.019). But religious beliefs had no significant role in the prediction of emotion-focused coping in mothers of children with ID compared with mothers of children without ID. Conclusion: In comparison with mothers of children without ID, religious beliefs were good predictors for problem-focused coping and personality dimensions (particularly neuroticism) were good predictors for emotion-focused coping in mothers of children with ID.